EFFECTIVENESS OF SENSORY STIMULATION ON LEVEL OF CONSCIOUSNESS AMONG TRAUMATIC BRAIN INJURY PATIENTS ADMITTED AT SELECTED TERTIARY CARE HOSPITAL, BHUBANESWAR, ODISHA – A RANDOMIZED CONTROLLED CLINICAL TRIAL (Journal of Pharmaceutical Negative Results, 2022)
Traumatic brain injury (TBI) is a complicated injury with a broad spectrum of symptoms and disabilities. The impact on an individual and their family will be devastating. A traumatic brain injury (TBI) is outlined as a force to the head or a penetrating cerebrum injury that disrupts the conventional operate of the cerebrum. TBI may result once the head suddenly and violently hits an object or when an object pierces the skull and enters cerebrum. Symptoms of a TBI can be mild, moderate or severe, counting on the extent of injury to the cerebrum. Mild cases might end in a quick amendment in mental state or consciousness, whereas severe cases might end in extended periods of unconsciousness, coma or may be death.